1996
DOI: 10.1111/j.1442-2042.1996.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Fournier's Disease: Adjunctive Hyperbaric Oxygen Therapy to Classic Therapy

Abstract: Fournier's disease is a very rare and highly fatal necrotizing fasciitis of genital and perineal tissues. Conventional treatment of Fournier's disease includes surgical debridement and antibiotic therapy. We describe a case of Fournier's disease where we added hyperbaric oxygen therapy to the conventional treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…The illness is more frequently seen in men with poor hygiene, diabetes, paraplegia, cirrhosis and in alcoholics 2,6−8,10,11 . The findings from the present study support these results because 17 patients were diabetics, although one study reported that diabetes is not a factor in the outcome 13 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The illness is more frequently seen in men with poor hygiene, diabetes, paraplegia, cirrhosis and in alcoholics 2,6−8,10,11 . The findings from the present study support these results because 17 patients were diabetics, although one study reported that diabetes is not a factor in the outcome 13 .…”
Section: Discussionsupporting
confidence: 82%
“…The pathology might be localized only to the scrotum or scattered to the penis, perineum, labia and abdominal wall 1−10 . FG may follow other colorectal and urinary system pathologies, infections and abscesses of the perineum, trauma to the penis or scrotum and any surgical interventions to the areas mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1883, when Jean Alfred Fournier first described what was then thought to be an idiopathic gangrene of the scrotum [ 4], the prognosis has been ominous. Mortality rates have been high despite the institution of a broad range of treatment protocols [ 5–9]. Over the past 3 years, the survival rate of our patients with Fournier’s gangrene has been high.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been recognised that the best treatment for synergistic gangrene is surgical excision, antibiotics having a secondary role. However, systemic corticosteroids [10] or adjunctive hyperbaric oxygen [1] could also play a therapeutic role. Since Fournier's gangrene is often, to "healthy" patients, wide incision and drainage of all involved areas and removal of all devitalized tissues should be performed as soon as the patient's medical condition allows.…”
Section: Discussionmentioning
confidence: 99%